2014
DOI: 10.1007/s10800-014-0691-1
|View full text |Cite
|
Sign up to set email alerts
|

Poly(acridine orange)-modified glassy carbon electrodes: electrosynthesis, characterisation and sensor application with uric acid

Abstract: Poly(acridine orange) was electropolymerised on glassy carbon electrodes by potential cycling in phosphate buffer solution at pH 5.5, 6.0, 7.0 and 8.0. Electrochemical behaviour of the modified electrodes was studied by cyclic voltammetry in phosphate buffer solution at various pHs and found that the best polymer film formation was obtained at pH 5.5. Quantitative determination of uric acid was achieved by cyclic voltammetry, differential pulse voltammetry (DPV) and fixed-potential amperometry in phosphate buf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…where Q is the charge corresponding to the polymer oxidation, Γ is the surface concentration of PMR, n is the number of electrons consumed in the electrode process, A is the electrode area (cm 2 ), and F is the Faraday constant , . It was assumed that two electrons were involved per monomer in the electropolymerization of MR in agreement with the literature .…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…where Q is the charge corresponding to the polymer oxidation, Γ is the surface concentration of PMR, n is the number of electrons consumed in the electrode process, A is the electrode area (cm 2 ), and F is the Faraday constant , . It was assumed that two electrons were involved per monomer in the electropolymerization of MR in agreement with the literature .…”
Section: Resultsmentioning
confidence: 98%
“…The anodic and the cathodic peaks of PMR films decreased in height significantly at higher pHs than 5.0. Dependence of the peak currents, I p , on scan rate, v , was investigated and found that both anodic and cathodic peak currents increased linearly with increasing scan rate for all PMR films (Table ), showing an adsorbed species‐controlled electrode process, similar to the polymer films in the literature , . In Table , the results of the linearity were listed for only the thickest three PMR films, since the peak currents of PMR films which were not listed in Table were too low to be analyzed.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations